2023
DOI: 10.1590/1984-0462/2023/41/2022092
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function of children and adolescents with osteogenesis imperfecta: respiratory muscle strength, forced vital capacity, and peak expiratory flow

Abstract: Objective: This study aims to evaluate the respiratory function of children and adolescents with osteogenesis imperfecta (OI) followed up at a referral center. Methods: A cross-sectional study was conducted with a non-probabilistic sample. Manovacuometry was performed with the measurement of maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP), and in addition, peak expiratory flow (PEF) and ventilometry were performed to measure forced vital capacity (FVC). Results: In total, 23 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…20 In children and adolescents with chronic lung diseases, telehealth interventions may contribute to improvements in HRQoL, treatment adherence, and better control of symptoms. 10 Consequently, they could also lead to better self-management of chronic lung diseases and prevention of exacerbations, thus preventing a decline in lung function. 1 Recently, a systematic review of seven RCTs reported the effectiveness of home-based rehabilitation on pulmonary function, functional capacity, and HRQoL in children and adolescents (6 to 20 years) with CF, emphasizing that home-based rehabilitation may be an alternative way of rehabilitation when conventional center-based programs are not able to be conducted for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In children and adolescents with chronic lung diseases, telehealth interventions may contribute to improvements in HRQoL, treatment adherence, and better control of symptoms. 10 Consequently, they could also lead to better self-management of chronic lung diseases and prevention of exacerbations, thus preventing a decline in lung function. 1 Recently, a systematic review of seven RCTs reported the effectiveness of home-based rehabilitation on pulmonary function, functional capacity, and HRQoL in children and adolescents (6 to 20 years) with CF, emphasizing that home-based rehabilitation may be an alternative way of rehabilitation when conventional center-based programs are not able to be conducted for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…9 Especially, using new technology in telehealth seems to be an opportunity for improving clinical outcomes such as symptom control, adherence to treatment, reduction of hospitalizations, and HRQoL in children and adolescents with chronic lung diseases. 10 Home-based remote rehabilitation combines the use of new technology and the home environment in the context of rehabilitation. When circumstances require the restriction of transports (e.g.…”
Section: Introductionmentioning
confidence: 99%